Antroponimic lexis of calendar type of ukrainian XIX century literary tale (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article analyses the peculiarities of calendar type lexis use by tale writers of the XIX century. It proves to combine the elements of Christian and folk perception and thanks to authors taking transfers folk natural knowledge to the future generation. Folk lexis is a personage itself with its formed characters.
Keywords: literary tale; antroponimic lexis; calendar lexis; personage